2010
DOI: 10.1016/j.otsr.2010.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Near-miss event assessment in orthopedic surgery: Antimicrobial prophylaxis noncompliance

Abstract: Level IV, Decision Analyses Study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 10 publications
0
21
0
1
Order By: Relevance
“…Orthopedic analysis of near misses and root causes is rare and has previously been reported regarding noncompliance with antimicrobial prophylaxis (Bonfait, Delaunay, de Thomasson, & Charrois, 2010). As such, this report is amongst the first in the orthopedic literature that demonstrates the efficacy of a near-miss analysis system.…”
Section: Discussionmentioning
confidence: 74%
“…Orthopedic analysis of near misses and root causes is rare and has previously been reported regarding noncompliance with antimicrobial prophylaxis (Bonfait, Delaunay, de Thomasson, & Charrois, 2010). As such, this report is amongst the first in the orthopedic literature that demonstrates the efficacy of a near-miss analysis system.…”
Section: Discussionmentioning
confidence: 74%
“…A French study in which surgeons were interviewed about the reasons for non-adherence to antibiotic GLs showed that the GLs were tailored to meet clinical needs and that non-application was because of negligence or lack of organisation [34]. It is therefore important to encourage all staff members to focus on organisational issues and to be involved in, or aware of, the assignment of specific responsibilities [52].…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, first generation cephalosporins, such as cefazolin, are the suggested first choice drugs [21,24,29]. Several studies show that the implementation of antibiotic prophylaxis is still extremely variable, despite the presence of national, regional and local GLs; antibiotics are used excessively and often inappropriately [30][31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enfin, le non-respect d'une antibioprophylaxie conforme aux protocoles des services a été rapporté dans 20 % des cas. Cette carence a déjà été relevée dans les enquêtes réalisées par Orthorisq et pourrait être améliorée par la pratique de la « check-list » proposée par la Haute Autorité de santé [28,29].…”
Section: Figureunclassified